2012
DOI: 10.1042/bj20112092
|View full text |Cite
|
Sign up to set email alerts
|

PI3K signalling in B- and T-lymphocytes: new developments and therapeutic advances

Abstract: Synopsis Activation of phosphoinositide 3-kinase (PI3K) is a shared response to engagement of diverse types of transmembrane receptors. Depending on the cell type and stimulus, PI3K activation can promote different fates including proliferation, survival, migration and differentiation. The diverse roles of PI3K signaling are well illustrated by studies of lymphocytes, the cells that mediate adaptive immunity. Genetic and pharmacological experiments have shown that PI3K activation regulates many steps in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
189
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(197 citation statements)
references
References 174 publications
(254 reference statements)
4
189
1
Order By: Relevance
“…Disruption of the MZ B cell subset is now recognized as a biomarker of p110␦ inhibition in mice (28,40). Genetic studies in mice suggest that a central signaling pathway governing MZ B cell development is initiated by CD19 on the cell surface, which signals via PI3K-p110␦ and AKT to suppress the transcription factor Foxo1 (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of the MZ B cell subset is now recognized as a biomarker of p110␦ inhibition in mice (28,40). Genetic studies in mice suggest that a central signaling pathway governing MZ B cell development is initiated by CD19 on the cell surface, which signals via PI3K-p110␦ and AKT to suppress the transcription factor Foxo1 (40).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies in mice suggest that a central signaling pathway governing MZ B cell development is initiated by CD19 on the cell surface, which signals via PI3K-p110␦ and AKT to suppress the transcription factor Foxo1 (40). Pharmacological inhibition of p110␦ using IC87114 reduces MZ B cell numbers but also disrupts their localization, with IgM hi /IgD lo B cells moving into the follicles (28).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt signaling plays a central role in B-cell activation and migration [11]. Genetic studies have shown that Akt1 and Akt2 are needed for the generation of MZ B cells and B1 B cells, but not of follicular B2 cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Important mediators downstream of Akt1 signaling include the tuberous sclerosis proteins 1 and 2 (TSC1/2), which regulate the activity of mTOR, a kinase controlling the activation of p70S6K and phosphorylation of ribosomal protein S6, and thus protein synthesis. Other prominent targets of Akt signaling are transcription factors of the NF-κB, NFAT, and FoxO families, which regulate the development, proliferation, and survival of B cells [7][8][9][10].PI3K/Akt signaling plays a central role in B-cell activation and migration [11]. Genetic studies have shown that Akt1 and Akt2 are needed for the generation of MZ B cells and B1 B cells, but not of follicular B2 cells [12,13].…”
mentioning
confidence: 99%
“…Indeed, inhibiting p110α alone can reduce the growth of tumors containing PIK3CA mutations (3), but this approach is not effective in all solid tumors. No oncogenic mutations have been identified in the other class I PI3K isoforms; however, p110δ-selective inhibitors have proven effective in the clinic in certain forms of leukemia (4).…”
Section: In the Spotlightmentioning
confidence: 99%